Napiętnowanie społeczne w chorobach przewlekłych - Markiewicz, Aleksandra; Gryglicka, Halina; Hozyasz, Kamil K. (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Regardless of diagnosis, chronic disease usually stigmatizes any patient. Social stigmatizing is one of the major risk factors for the quality of an individual’s psychosocial functioning. Because of label of disease, patient is often ostracized. Social rejection equals a decline in mood and self-esteem. It also threatens emotional, social and intellectual growth of patients, particularly in developmental age. Limitation of peer contacts and lack of self-esteem may contribute to a loss of motivation. Such a condition often leads to discontinuation of medical recommendations. The stigma of the disease exerts a strong influence on the whole family system. Both patient’s parents and siblings struggle with burden, whose negative consequences are reflected in family’s and social’s relationships as well as daily functioning. This paper discusses the definition, mechanism of the phenomenon, and consequences of social stigma, as well as presents literature review relating to stigmatization in the context of selected chronic diseases and family burden.